Mechanisms associated with post-stroke depression and pharmacologic therapy - Zhan, Qingyang; Kong, Fanyi (Frontiers in Neurology, 2023)
Stroke is one of the most common cerebrovascular diseases, which is the cause of long-term mental illness and physical disability, Post-stroke depression (PSD) is the most common neuropsychiatric complication after stroke, and its mechanisms are characterized by complexity, plurality, and diversity, which seriously affects the quality of survival and prognosis of patients. Studies have focused on and recognized neurotransmitter-based mechanisms and selective serotonin-reuptake inhibitors (SSRIs) can be used to treat PSD. Neuroinflammation, neuroendocrinology, neurotrophic factors, and the site of the stroke lesion may affect neurotransmitters. Thus the mechanisms of PSD have been increasingly studied. Pharmacological treatment mainly includes SSRIs, noradrenergic and specific serotonergic antidepressant (NaSSA), anti-inflammatory drugs, vitamin D, ect, which have been confirmed to have better efficacy by clinical studies. Currently, there is an increasing number of studies related to the mechanisms of PSD. However, the mechanisms and pharmacologic treatment of PSD is still unclear. In the future, in-depth research on the mechanisms and treatment of PSD is needed to provide a reference for the prevention and treatment of clinical PSD.